RESTOCKING UNTUK KONSERVASI IKAN BADUT GIRU (Amphiprion clarkii) PADA WILAYAH PERAIRAN NEGERI SULI, KECAMATAN SALAHUTU, KABUPATEN MALUKU TENGAH - Sahusilawane, Helena Afia; Karuwal, Ritha L.; Slamet, Heru (Jurnal Abdi Insani, 2024)
Suli village is one of the areas in Maluku Islands which has natural resources and high water aesthetic value so that it is used as an ecotourism area both domestically and internationally. However, currently the potential of its waters is experiencing a decline in population due to the activities of local communities. One of them is excessive fishing of marine ornamental fish for market purposes and food needs. One type of marine ornamental fish that is caught is the giru clownfish (Amphiprion clarkii). To preserve this type of ornamental fish, conservation efforts are needed so that it remains sustainable and conserved. One of them is restocking to increase fish stocks in nature. In this regard, the service team as part of environmental and fisheries observers felt it was necessary to carry out the activities. This activity began with cultivation phase Ambon Sea Aquaculture Fisheries Center, coordinating situation analysis in the waters of Suli, surveying restocking locations and restocking activities and then monitoring and evaluation. The results of this activity show that the service team succeeded in cultivating giru clownfish from 3 pairs of broodstocks and produced fry four times after hatching. The results of seed maintenance were followed by restocking as many 600 individual giru clownfish seeds measuring 5 cm at three spots. Based on monitoring and evaluation results, the fish seeds are able to adapt and survive in different environmental conditions. Thus, conservation efforts are needed through continue restocking of ornamental fish to maintain resource potential and increase opportunities for sustainable ecotourism.